A review of swirl air intake effect on the performance of a compression ignition engine - Mohd Alias, Mohd Shahrudin; Hairuddin, Abdul Aziz; Hassan, Mohd Khair; Md Rezali, Khairil Anas (National University of Malaysia, 2025)
Compression Ignition (CI) engines are highly efficient power sources compared to Spark Ignition (SI) engines and currently play a significant role in the transportation and industrial sectors. However, the engine has constraints with low engine performance, high fuel consumption and emissions levels which require continuous improvement. There are various designs of air intake systems to meet a specific engine operating range, still, there will be less actual amount of fresh charge entering the cylinder compared to the theoretical value due to the short cycle time available. The application of the existing air intake system becomes the main focus since the air resistance presented in the system is causing more pressure drop, reducing volumetric efficiency. This requires a comprehensive review of the patented or commercial air intake devices in proposing an improved air intake manifold design. Swirl in the intake air is an additional characteristic knowingly able to increase the fuel and air mixing rate for better combustion, thus reducing the exhaust gas emissions. However, the air resistance may also reduce the efficiency of the air swirl formed within the intake manifold, thus restricting the potential for combustion improvement. Numerous studies have been conducted to evaluate the effect of swirl air intake in the compression ignition engine due to the continuous issue of emission quality. Differences in intake designs, flow characteristics, numerical study, and other issues associated with engine performance are also thoroughly discussed in this review paper.